2011
DOI: 10.1093/aob/mcr314
|View full text |Cite
|
Sign up to set email alerts
|

Effects of soil nutrient heterogeneity on intraspecific competition in the invasive, clonal plant Alternanthera philoxeroides

Abstract: Results indicate that fine-scale, spatial heterogeneity in the availability of soil nutrients does not increase competition when plants are genetically identical, consistent with the suggestion that effects of heterogeneity on competition depend upon differences in plasticity between individuals. Heterogeneity is only likely to increase the spread of monoclonal, invasive populations such as that of A. philoxeroides in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 39 publications
(53 reference statements)
1
62
1
Order By: Relevance
“…Wijesinghe and Hutchings1415 found a negative correlation between the performance (biomass) of the stoloniferous herb Glechoma hederacea and patch size. Moreover, Zhou et al 43. suggested that heterogeneity might be a significant driving factor of clonal plant invasion if a strong, positive response to fine-scale nutrient heterogeneity is common.…”
Section: Discussionmentioning
confidence: 99%
“…Wijesinghe and Hutchings1415 found a negative correlation between the performance (biomass) of the stoloniferous herb Glechoma hederacea and patch size. Moreover, Zhou et al 43. suggested that heterogeneity might be a significant driving factor of clonal plant invasion if a strong, positive response to fine-scale nutrient heterogeneity is common.…”
Section: Discussionmentioning
confidence: 99%
“…More broadly, plants often suffer from harsh environmental conditions within their current and potential distribution ranges. However, while many studies have focused on the tolerance to low resource availability and competition under different levels of resource availability (Grime 1977, Tilman 1985, Tilman 1990, Grace 1991, Li et al 2011, Zhou et al 2012, the effects of the tolerance of new arrivals to non-resource factors on their performance and competitiveness have been relatively ignored.…”
Section: Introductionmentioning
confidence: 99%
“…In response to substrate nutrient heterogeneity, many species show variation in how their roots are arranged in the substrate where nutrient levels are relatively high. Many studies have found that the effects of substrate nutrient heterogeneity may increase plant performance across all growth parameters [19][20][21][22]. Substrate nutrient heterogeneity may work as a modulator by changing plant growth at the individual and community levels.…”
Section: Introductionmentioning
confidence: 99%